Circulating soluble E-selectin in early rheumatoid arthritis: a prospective five year study. Issue 3 (1st March 2002) - Kuuliala, A; Eberhardt, K; Takala, A; Kautiainen, H; Repo, H; Leirisalo-Repo, M
Abstract : Background: Soluble E-selectin (sE-selectin) is a marker of activation of vascular endothelium. Objective: To examine serum levels of sE-selectin in a cohort of 85 patients with early rheumatoid arthritis (RA) followed up for five years. Methods: sE-selectin levels were assessed annually using an enzyme linked immunosorbent assay (ELISA) and related to simultaneously obtained clinical and laboratory measures. Joint inflammation was evaluated by active joint count, functional status by Health Assessment Questionnaire (HAQ), and radiographic findings in hands and feet by the Larsen method. Laboratory tests included serum C reactive protein (CRP) level, erythrocyte sedimentation rate, blood haemoglobin level, white blood cell count (WBC), and platelet count. Area under the curve (AUC) was calculated for each variable, and Jonckheere's test for ordered alternatives was applied to assess significance of association between sE-selectin AUC tertiles and other variables. Baseline sE-selectin tertiles were related to change in Larsen score and HAQ score at five years. Odds ratios (OR) with 95% confidence interval (CI) were calculated using univariate and multivariate logistic regression. Results: sE-selectin levels were associated with CRP level (p=0.012), WBC (p=0.037), active joint count (p=0.019), progression of joint destruction (p=0.038), and HAQ score at five years (p=0.021), but not with extra-articular symptoms or comorbidity. Baseline sE-selectin levels in the third tertile predicted the HAQ score at five years (OR 4.18, 95% CI 1.15 to 15.22). sE-selectin levels of patients did not differ significantly from those of healthy control subjects. Conclusion: The degree of activation of vascular endothelium is associated with activity and outcome of early RA.